2007
DOI: 10.1007/bf03349227
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thyroidectomy on psychiatric symptoms and quality of life

Abstract: Our results indicate that even long after euthyroidism is achieved after surgery, patients show a significant improvement of mental health and a reduction of psychiatric symptoms. Nevertheless, patients continue to have a poorer QOL compared to the Italian normative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
3
11
0
1
Order By: Relevance
“…In an Italian population with thyroid disorders, Bianchi et al (2004) used the SF-36 inventory and Nottingham health profile to evaluate health-related QoL; this was found to be poor regardless of the severity and functional type of thyroid dysfunction, as already shown by other studies (Jaeschke et al, 1994;Ljunggren et al, 1998;Biondi et al, 2000). In a cohort of patients scheduled for thyroid surgery for several reasons, including cancer in 17% of cases, Miccoli et al (2007) assessed QoL by means of the SF-36 inventory, but not the Symptom Checklist-90; they found poorer overall scores and social functioning than in either the general population or patients scheduled for nonthyroidal surgery. Thyroidectomy was followed by a significant reduction in the severity of psychiatric symptoms, but social functioning remained markedly impaired for a long time, even after euthyroidism had been achieved (Miccoli et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In an Italian population with thyroid disorders, Bianchi et al (2004) used the SF-36 inventory and Nottingham health profile to evaluate health-related QoL; this was found to be poor regardless of the severity and functional type of thyroid dysfunction, as already shown by other studies (Jaeschke et al, 1994;Ljunggren et al, 1998;Biondi et al, 2000). In a cohort of patients scheduled for thyroid surgery for several reasons, including cancer in 17% of cases, Miccoli et al (2007) assessed QoL by means of the SF-36 inventory, but not the Symptom Checklist-90; they found poorer overall scores and social functioning than in either the general population or patients scheduled for nonthyroidal surgery. Thyroidectomy was followed by a significant reduction in the severity of psychiatric symptoms, but social functioning remained markedly impaired for a long time, even after euthyroidism had been achieved (Miccoli et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…In a cohort of patients scheduled for thyroid surgery for several reasons, including cancer in 17% of cases, Miccoli et al (2007) assessed QoL by means of the SF-36 inventory, but not the Symptom Checklist-90; they found poorer overall scores and social functioning than in either the general population or patients scheduled for nonthyroidal surgery. Thyroidectomy was followed by a significant reduction in the severity of psychiatric symptoms, but social functioning remained markedly impaired for a long time, even after euthyroidism had been achieved (Miccoli et al, 2007). One obstacle to evaluating illness perception in patients with thyroid cancer is the current lack of developed questionnaires (Watt et al, 2010) like that used for thyroid-associated ophthalmopathy (Terwee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in euthyroid patients the influence of hormonal status on QoL is irrelevant, it can be assumed that surgical therapy itself influences the postoperative QoL. In this context, it has been shown that thyroidectomy improves sleep apnoea symptoms, as well as swallowing‐related QoL, and can positively influence psychiatric symptoms . For the evaluation of QoL in nontoxic benign goitre, a disease‐specific questionnaire has been established in Denmark and is now used in further countries, except for German‐speaking countries, as it is not validated currently.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery seems to improve postoperative QoL in patients with benign goitres using generic and disease‐specific questionnaires . For instance, the Thyroid Patient‐Reported Outcome (ThyPRO), a disease‐specific questionnaire, has been recommended for use in patients with benign thyroid diseases, but a German version of this questionnaire has not been validated yet.…”
Section: Introductionmentioning
confidence: 99%